Experimental Study on the Inner Set Bolted Joint of Steel Tube Subject to Axial Pressure - Chao, Huang; Li, Xing (Materials Science Forum, 2016)
This paper presents an experimental investigation about the inner set bolted joint of steel tube subject to axial pressure. In total six tests which the thickness and the length of the cross plate were considered, were conducted. The tests results showed that, the inner set bolted joint can effectively transfer axial force, but can be easy to cause stress concentration and uneven distribution of the stress at the section break. So the inner set bolted joint should be considered the shear lag effect in design. In addition, increasing the length and the thickness could increase the test efficiency.